The Effect Of Blue Methyl Concentration And Contact Time Toward Stain Resistance Tests On Sanytaryware Glaze - Hendra Kustiawan; Muhammad Syaifun Nizar (Jurnal Keramik dan Gelas Indonesia, 2019)
The applications of sanitaryware glazed ceramics were exposed to a chemical substance that can leave a stain. One of the example are sanitaryware glaze which according to SNI 797:2018 must pass stain test to comply with the standard. On the SNI 797:2018 stain test procedure, one of the chemicals used are blue methyl with 0,5% concentration and 1 hour contact time. The purpose of this research is to investigate the effect of concentration and contact time duration on the stain resistance result test. Stain resistance test was carried out with methyl blue concentration 0,1-0,5% and contact time 1-24 hour on 540 samples and calculated with statistic which 461 (85.37%) samples pass stain test or unstained, and 79 (14.63%) samples failed stain test or stained. In the statistical calculation the concentration range of the dye is 0.1% -1.5% and the contact time of 1-24 hours is calculated as many as 400 samples. Concentration and contact time have a positive effect and significant on stain resistance test with a regression coefficient of 0,12% for stain color concentration and 0.92% for contact time. Based on the coefficient result, the effect of contact time is greater than the stain color concentration on the stain resistance test.